Decoding the enigmatic estrogen paradox in pulmonary hypertension: delving into estrogen metabolites and metabolic enzymes - Qiang You; Hequn Song; Ziming Zhu; Jinzheng Wang; Ruixin Wang; Mingjia Du; Yingjie Fu; Jinxiang Yuan; Rubin Tan (Cellular & Molecular Biology Letters)
Abstract Pulmonary hypertension (PH) presents a puzzling sex bias, being more prevalent in women yet often less severe than in men, and the underlying reasons remain unclear. Studies using animal models, and limited clinical data have revealed a protective influence of exogenous estrogens, known as the estrogen paradox. Research suggests that beyond its receptor-mediated effects, estrogen acts through metabolites such as 2-ME2, 4-OHE2, and 16-OHE2, which are capable of exhibiting protective or detrimental effects in PH, prompting the need to explore their roles in PH to untangle sex differences and the estrogen paradox. Hypoxia disrupts the balance of estrogen metabolites by affecting the enzymes responsible for estrogen metabolism. Delving into the role of these metabolic enzymes not only illuminates the sex difference in PH but also provides a potential rationale for the estrogen paradox. This review delves into the intricate interplay between estrogen metabolites, metabolic enzymes, and PH, offering a deeper understanding of sex-specific differences and the perplexing estrogen paradox in the context of this condition. Graphic Abstract